Comparison of grab start between elite and trained swimmers - Vantorre, J.; Seifert, L.; Fernandes, R. J.; Vilas-Boas, J. P.; Chollet, D. (International Journal of Sports Medicine, 2010)
This study analysed motor control during front crawl swimming starts by elite and trained swimmers, based on comparisons of: 1) kinematic and kinetic parameters of the start and 2) variability of these parameters across 3 trials per swimmer. Given that the start time to the 15-m mark is greatly influenced by the swimming phase, the study also compared the stroking and coordinative parameters from water entry to 25-m in the 2 skill groups. The swimmers performed 3×25-m at the 50-m race-pace and used their preferential start technique (grab start). The elite swimmers showed better start organization as reflected by higher impulse values in the direction of intended displacement despite similar block phase durations. They then spent more time in the water entry, gliding and leg kicking phases, with shorter swimming phase duration and 15-m start time than the trained swimmers (p<0.05). The trained swimmers showed significantly lower values for stroke length and velocity (p<0.05) during the swimming phase. Analysis revealed low intra-subject variability (across the 3 trials) but high inter-subject variability, indicating that both elite and trained swimmers had mastered distinct, though different, motor patterns.